Pengaruh Pemberian Pembenah Tanah dan Pupuk NPK terhadap Pertumbuhan dan Hasil Tanaman Tomat (Lycopersicum esculentum) Varietas Mawar. - Fenty Sri Bintang Khoiriyah Bintang Khoiriyah; Agus Sugianto; Sunawan Sunawan (Folium : Jurnal Ilmu Pertanian, 2022)
Tomato is one of the plants whose fruit has good selling and nutritional value. Provision of soil amendments can reduce the need for excessive inorganic fertilizers on tomato plants. This study aims to determine the effect of soil amendment and NPK fertilizer on the growth and yield of tomato (Lycopersicum esculentum) plants. This research was conducted on farmer's land, Singosari District, Malang Regency with an altitude of 600 m above sea level. Average temperature 22 - 320C. This study used a factorial randomized block design (RAK) consisting of 10 treatments consisting of 2 combinations of soil enhancer (without soil enhancer, with soil enhancer) with 5 doses of NPK fertilizer (0. 25%, 50%, 75%, 100%). . The results showed that the treatment of soil amendment  with 25% NPK fertilizer could increase the growth of tomato plants. Treatment of soil improver  with 25% NPK fertilizer) can increase the yield of fresh fruit weight and tomato harvest index